Determination of Trace Elements in Patients with Chronic Hepatitis B - Saeid Abediankenari; Maryam Ghasemi; Mohammad Mahdi Nasehi; Siavash Abedi; Vahid Hosseini (Acta Medica Iranica, 2011)
Chronic Hepatitis B virus (HBV) infection is a major liver disease worldwide and its clinical manifestations are linked to immune response. The purpose of this study was to evaluate the relationship between selenium, copper, and zinc in comparison with transaminase level in chronic HBV patients. Serum samples of the HBV infected patients were obtained from Tooba medical center, Sari, Iran. Sixty patients were enrolled in this study (36 men and 24 women), mean age: 39.6 ± 12.2 years. The concentration of zinc, selenium, copper and transaminases were determined using an autoanalyzer system. Concentrations of selenium (0.273 ±0.056 μg/dl) and zinc (2.1±0.037) was elevated in patients with low transaminase levels as were significantly different in comparison with patients with high transaminase level (P<0.05). Serum copper concentration was similar in two groups of patients. Elevated levels of transaminase concentrations were independently associated with low zinc and selenium concentrations in chronic HBV patients. It is concluded that serum zinc and selenium levels are associated with less hepatic damage in chronic HBV patients and might have a protective role during liver injury.